Angiopoietin-like protein 3: a novel potential biomarker for nephrotic syndrome in children - Wen, Fujie; Liu, Junchao; Dai, Rufeng; Hong, Sha; Ji, Baowei; Liu, Jiaojiao; Zhang, Jun; Han, Xinli; Lv, Qianying; Liu, Jialu; Shen, Qian; Xu, Hong (Frontiers in Pediatrics, 2023)
Background Angiopoietin-like 3 (ANGPTL3) is a secretory glycoprotein. It has been demonstrated that ANGPTL3 level was upregulated in minimal change nephrotic syndrome (MCNS) kidney tissues. Subsequently, our group found that ANGPTL3 level was closely correlated with nephropathy in vivo and in vitro. Hence, whether ANGPTL3 level could be correlated with the proteinuria level, and assessment of disease severity of nephrotic syndrome (NS) remained to be investigated. This study aimed to analyzed the correlation between the levels of ANGPTL3 in serum and urine of patients with nephrotic syndrome and proteinuria, and assessed the severity of the patients' disease. In future clinical translation, the level of ANGPTL3 in serum, urine will be used as a biomarker to better predict the development of nephrotic syndrome. Methods A total of 200 NS patients and 80 healthy controls (age, 1-18 years) were admitted to our institution between 2021 and 2022. The etiology of NS included primary nephrotic syndrome (PNS, n=144) and NS with other causes (n=56). A total of 280 serum samples and 244 urinary samples were collected to determine ANGPTL3 level using enzyme-linked immunosorbent assay (ELISA). Results Serum ANGPTL3 and urinary ANGPTL3/Cre were remarkably elevated in NS patients compared with those in healthy controls. Furthermore, serum ANGPTL3 and urinary ANGPTL3/Cre were significantly correlated with proteinuria level. Additionally, multivariate linear regression analysis demonstrated that serum ALB was independently correlated with serum ANGPTL3 and PRO/CR was independently correlated with urinary ANGPTL3/Cre in NS patients. Conclusion Serum ANGPTL3 and urinary ANGPTL3/Cre showed a promising performance in the diagnosis of NS,and served as novel potential noninvasive biomarkers to assess disease severity of NS. Further exploration of the role of ANGPTL3 level may shed a new light on the treatment of NS.